Islamic Economic Dispute Resolution - Nazwa Sabrina Naslim; Mohammad Amir Bin Wan Harun (Program Pascasarjana UIN Sumatera Utara Medan, 2022)
The rapid development of Islamic economics and finance in Indonesia has increased the potential for disputes due to differing understandings of contracts, breaches of contract, and inconsistencies in practices with Islamic principles. This situation demands a dispute resolution mechanism that can guarantee legal certainty while remaining grounded in Islamic values. This study aims to examine the definition and causes of Islamic economic disputes, the principles for their resolution, available mechanisms, and the authorized institutions in Indonesia. The method used is a normative juridical approach with an analysis of Islamic legal sources and relevant legislation. The study results show that, from an Islamic legal perspective, dispute resolution emphasizes the principles of justice (al-'adl), public interest (al-maslahah), and balance (tawazun) through deliberation (shura), reconciliation (sulh), and arbitration (tahkim). Meanwhile, under Indonesian positive law, dispute resolution is conducted through litigation in Religious Courts and non-litigation methods such as mediation and arbitration through BASYARNAS. These two approaches complement each other by ensuring legal certainty, efficiency, and compliance with sharia principles. Thus, the resolution of Islamic economic disputes in Indonesia is an integration of Islamic law and positive law that not only aims to resolve conflicts, but also maintains the values of justice, ethics, and sustainability of the Islamic economy.